Classification of two-dimensional Jordan algebras over R - Bekbaev, Ural; Rakhimov, Isamiddin; Ahmed, Houida (Universiti Putra Malaysia, 2018)
In the paper we describe all (not necessarily commutative) Jordan algebra structures on a two-dimensional vector space over R in terms of their matrices of structure constants.